David in the desert: tradition and redaction in the “History of David’s rise" - Bezzel, Hannes; Kratz, Reinhard Gregor (Beihefte zur Zeitschrift für die alttestamentliche Wissenschaft, 2021)
Frontmatter -- Preface -- Contents -- Introduction -- David in the Judean Desert -- Saul, David und die Entstehung der Monarchie in Israel -- The Land “from Telam on the way to Shur and on to the land of Egypt” (1 Sam 27) -- All the גבול of Israel (1 Sam 27:1) -- Der Mann, mit dem Gott war. Kompositions- und quellenkritische Überlegungen zur Darstellung des Aufstiegs Davids in den Samuelbüchern -- David and his Alter Ego in the Desert -- Saul and David – Stages of Their Literary Relationship -- On a Redaction Technique in 1 Sam 19:18–21:1 -- David and the Priests of Nob: Collusion or Illusion? -- David’s Flight to the King of Gath -- David and Achish: Remembrance of Things Past, Present, or Future? -- David in Keïla -- “David is Hiding among Us” -- Wilderness, Liminality and David’s Rite of Passage -- Der Spieß wird umgedreht -- General Index -- Index of Selected Text Passages